An Interdisciplinary Approach and Advanced Techniques for Enhanced 3D-Printed Upper Limb Prosthetic Socket Design: A Literature Review - Kai Xu; Shengfeng Qin (Actuators, 2023)
This review investigates the opportunities and challenges of interdisciplinary research in upper limb prosthetic (ULP) socket design and manufacturing, which is crucial for improving the lives of individuals with limb loss. By integrating various disciplines, such as engineering, materials science, biomechanics, and health care, with emerging technologies such as 3D printing, artificial intelligence (AI), and virtual reality (VR), interdisciplinary collaboration can foster innovative solutions tailored to users’ diverse needs. Despite the immense potential, interdisciplinary research faces challenges in effective communication, collaboration, and evaluation. This review analyses pertinent case studies and discusses the implications of interdisciplinary research, emphasizing the importance of fostering a shared understanding, open communication, and institutional innovation. By examining technological advancements, user satisfaction, and prosthetic device usage in various interdisciplinary research examples, invaluable insights and direction for researchers and professionals seeking to contribute to this transformative field are provided. Addressing the challenges and capitalizing on the opportunities offered by interdisciplinary research can significantly improve upper limb prosthetic socket design and manufacturing, ultimately enhancing the quality of life for users worldwide.